Oligodendrocyte Progenitor Cells in the Adult Rat CNS Express Myelin Oligodendrocyte Glyco‐protein (MOG) - Li, Guilin (Brain Pathol, 2006)
While the effects of high dose X‐irradiation on mitotically active progenitor cells and remyelination are well‐documented, its effects on myelinating oligodendrocytes are less clear, due in part to divergent views on their mitotic capacity. To examine the effect of X‐irradiation on oligodendrocytes, the spinal cord of rats was exposed to 40 Gy of X‐irradiation and the number of oligodendrocytes and oligodendrocyte progenitors in the dorsal funiculi at T12 and L1 was determined by in situ hybridization using cRNA‐probes for platelet derived growth factor alpha receptor (PDGFRα) (to identify oligodendrocyte progenitors), exon 3b of proteolipid protein (PLP) (to identify mature oligodendrocytes) and myelin oligodendrocyte glycoprotein (MOG). X‐irradiation resulted in no change in the number of PLP positive cells and no loss of myelin internodes, but caused an almost complete loss of PDGFRα‐expressing cells, and a reduction in the number of MOG positive cells to a number similar to that found using the PLP exon 3b probe. Importantly, the number of radiation‐sensitive MOG‐expressing cells was similar to the number of PDGFRα positive cells. To determine if the radiation‐sensitive MOG positive cells were the same population as the radiation sensitive PDGFRα‐expressing cells, MOG and PDGFRα‐expressing cells were isolated from the adult CNS using antibody coated magnetic beads. Twelve to thirteen percent of MOG positive cells were PDGFRα positive and nearly all the PDGFRa isolated cells were MOG and galactocerebroside positive. Double immunofluorescence revealed colocalization of NG2 and MOG on cells in the normal adult rat spinal cord. These results show that in situ in the adult rat spinal cord white matter oligodendrocyte progenitors are MOG positive and indicates that expression of MOG cannot be regarded a marker that only identifies mature myelin‐supporting oligodendrocytes in tissue.